Application of problem-based learning (PBL) learning model to improve long jump learning outcomes in class x 1 students of SMA negeri 2 Tabanan - Ni Kadek Rani Puspa Nirmala Sari; I Made Satyawan; I Ketut Semarayasa (Physical Education Departement of University PGRI Jombang, 2025)
This research aimed to improve long jump learning outcomes in class X 1 students of SMA Negeri 2 Tabanan by applying the Problem-Based Learning learning model. This type of classroom action research was carried out in two cycles: action planning, implementation, observation, and reflection. The research subjects were class X 1 students of SMA Negeri 2 Tabanan in the academic year 2023/2024. There were 36 students, consisting of 20 females and 16 males. Data were analyzed using descriptive statistical analysis. The results showed that learning outcomes classically experienced a significant increase in the attitude aspect from cycle I of 16.7% increased to 80.6% in cycle II, the knowledge aspect from cycle I of 44.4% increased to 86.1% in cycle II, and the skill aspect from cycle I of 33.3% increased to 80.6% in cycle II. The research concluded that the learning outcomes of the long jump increased through the application of the PBL learning model in class X 1 students of SMA Negeri 2 Tabanan in the academic year 2023/2024. Therefore, this research recommends PE teachers consider using the PBL learning model because it can improve long jump learning outcomes.